COMMUNITY BASED COMMON POOL RESOURCES MANAGEMENT MODEL - Fatchul Annaji, Muhammad; Muhammad , Adji Suradji (Journal of Indonesian Rural and Regional Government, 2024)
Springs are one of the common pool resources whose ownership cannot be controlled by individuals. This is because common pool resources are used by many people. Gunungkidul Regency is an area that has limited water resources. Katongan District has a spring which is a source of clean water for the community. This research examines the management model for springs which become common pool resources as a source of clean water. By using a qualitative descriptive approach and supported by information from competent parties, both directly and indirectly, regarding the management of common pool resources, it is hoped that an ideal management model will be found. The research results show that the springs which are common pool resources in Katongan District are managed by the community around the springs. This can be seen from the management plan which was designed together by forming a spring management group called Sumber Agung, then the community worked together to carry out pipework to distribute clean water. Next, an evaluation is carried out every month which is carried out independently to control the management which is carried out jointly.